KEADILAN RESTORATIF DAN REVITALISASI LEMBAGA ADAT DI INDONESIA - Eva Achjani Zulfa (Jurnal Kriminologi Indonesia, 2010)
This paper is intended to explored the revitalization of local custom or traditional institutions due to restorative justice concept and its implementation. Depicting several examples from other nations, the writer then describes potential problems within local custom or tradition in Indonesia whilst implementing restorative justice.